Cytotoxicity in vitro assay in 3D vs. 2D L929 cell cultures – comparative analysis of the response to the latex extracts - Beata Gruber-Bzura; Irena Bubko; Lidia Mielczarek; Anna Pogorzelska; Katarzyna Wiktorska (PLoS ONE, 2026)
The ISO 10993–5 recommends the cytotoxicity in vitro tests of the medical devices for the 2D cultures. The aim of the study was: – to develop the L929 cell cultures in the 3D model; – to adapt the above tests for the 3D L929 cell culture using the latex extracts; – to define how the model of the cell culture affect the response of the cells in terms of morphology, viability and the expression of Bax, Bcl2, Jkamp, Pidd1 and Cyp3a44 genes, and – to check whether this potential response depends on the cell age. To achieve these goals the optical and confocal microscopy, the LDH test and RT-qPCR technique were used. The L929 cells are relatively easy to culture in the 3D model The 10 3– 10 5 cells/well were selected as optimal for the L929 spheroid formation. Generally, the 3D L929 cell cultures were less sensitive to the latex extracts than the 2D. The visible cytotoxic effects were noted regardless the age of cells, after 48 hrs. However, the spheroids of the older cells, after 72 hrs of exposure neutralized the cytotoxic effects and were regenerated. This effect was also confirmed in the LDH test and may be related to the high expression of the Bax gene.The expression of all analysed genes were changed in the 3D conditions. The cytotoxicity in vitro studies using the 3D model imposed certain limitations that are not present in the traditional model. Firstly, a limitation is the cell age, as the older L929 cells have been shown to be more sensitive to the cytotoxic agent. Secondly, for the older cells, a limitation may be the exposure time, given the potential for the spheroid regrowth.